An Analysis Of The ESP Textbook 'English For Specific Purposes For Meetings' Based Tomlinson's Theory - Abdul Syahid; Ahmad Julianto; Alvin Maulana; Muhammad Rafi Zidan; Muhammad Hidayatur Rahman (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
This study evaluates the effectiveness of the "English for Specific Purposes for Meetings" textbook authored by Kenneth Thompson, published by OXFORD University Press, through a descriptive analysis method. Drawing on Tomlinson's theoretical criteria, the evaluation highlights the textbook's alignment with learner needs and its efficacy in fostering engagement and confidence in professional communication settings. Findings indicate that the textbook effectively integrates contemporary topics and diverse learning activities to support authentic language use and active learning. However, a notable area for improvement is the need for outcome feedback opportunities. Overall, while the "English for Meetings" textbook demonstrates substantial effectiveness in addressing learner needs within professional contexts, areas for enhancement exist, suggesting avenues for future research to inform improved language teaching practices for ESP learners.